La representación fílmica del sexo en la vejez: un estudio de casos en el cine contemporáneo - Dra. Irene LIBERIA VAYÁ,Dr. Sergio COBO DURÁN (Fonseca, Journal of Communication, 2023)
Do eroticism and sexual desire die out with age? If we look at what cinema reveals, the answer is an (almost) unequivocal yes. This deep-rooted cultural taboo is also presented in cinema and exemplified by the few occasions in which films have broken such taboo over its more than 120 years of history